Regards croisés sur un Centenaire. Un premier bilan des commémorations de la Première Guerre mondiale à Bruxelles - Serge Jaumain; Joost Vaesen; Bruno Benvindo; Pierre Bouchat; Eric Bousmar; Iadine Degryse; Chantal Kesteloot; Olivier Klein; Karla Vanraepenbusch (Brussels Studies)
The centenary of World War I has marked an abrupt change: historical events will never be commemorated in the same way, especially in Belgium. The federated entities have demonstrated the autonomous role which they intend to play in future events of this type. The Brussels-Capital Region was not outdone. While the political choice to be directly involved in the commemorative events was made later there than in the other main regions and communities, it demonstrated its will and capacity to implement different activities aimed at reaching a very wide public. The systematic study of just over 430 activities identified between January 2014 and June 2017 in the territory of the Brussels-Capital Region thus highlights their extreme diversity as well as the exceptional dynamism of the municipalities which were at the origin of one quarter of them. Overall, the theme of the majority of events studied wavered between two main lines: the daily life of the inhabitants of Brussels and the global history of the conflict in its Belgian dimension. But these approaches were also used to prompt debates and reflection on current issues which make sense in today's society: the defence of freedom, solidarity, democracy, social cohesion, etc. The historical approach was therefore used as a tool for cohesion and as a lever for integration, with a past which concerns everybody: the inhabitants of Brussels from here and elsewhere, history enthusiasts, lovers of historical memory tourism, non-natives, expatriates, tourists for a day, etc.